Effect of endosulfan on blood gases in the edible fish Oreochromis mossambicus (Peters) - Rangaswamy, C P (Indian Journal of Fisheries, 2011)
Oxygen capacity, oxygen and carbon dioxide contents of blood of controlO. mossambicus were 14.33, 4.06 and 8.01 vol. % respectively. Upon exposureto sublethal and lethal concentrations of endosulfan, the oxygen content ofblood decreased, while the carbon dioxide content increased. Blood pHdecreased due to increase in its C02 content. Derangement in blood gas levelsunder endosulfan toxicity signifies inability of the pigment to carry out itsnormal respiratory functions. This calls for careful application of pesticides toprotect inland water life including fish.